Effect of moderate to high intensity aerobic exercise on blood pressure in young adults: The TEPHRA open, two-arm, parallel superiority randomized clinical trial - Williamson, Wilby; Lewandowski, Adam James; Huckstep, Odaro John; Lapidaire, Winok; Ooms, Alexander; Tan, Cheryl; Mohamed, Afifah; Alsharqi, Maryam; Bertagnolli, Mariane; Woodward, William; Dockerill, Cameron; McCourt, Annabelle; et al. (EClinicalMedicine, 2022)
Exercise is advised for young adults with elevated blood pressure, but no trials have investigated efficacy at this age. We aimed to determine whether aerobic exercise, self-monitoring and motivational coaching lowers blood pressure in this group. The study was a single-centre, open, two-arm, parallel superiority randomized clinical trial with open community-based recruitment of physically-inactive 18–35 year old adults with awake 24 h blood pressure 115/75mmHg-159/99 mmHg and BMI<35 kg/m2. The study took place in the Cardiovascular Clinical Research Facility, John Radcliffe Hospital, Oxford, UK. Participants were randomized (1:1) with minimisation factors sex, age (<24, 24–29, 30–35 years) and gestational age at birth (<32, 32–37, >37 weeks) to the intervention group, who received 16-weeks aerobic exercise training (three aerobic training sessions per week of 60 min per session at 60–80% peak heart rate, physical activity self-monitoring with encouragement to do 10,000 steps per day and motivational coaching to maintain physical activity upon completion of the intervention. The control group were sign-posted to educational materials on hypertension and recommended lifestyle behaviours. Investigators performing statistical analyses were blinded to group allocation. The primary outcome was 24 h awake ambulatory blood pressure (systolic and diastolic) change from baseline to 16-weeks on an intention-to-treat basis. Clinicaltrials.gov registered on March 30, 2016 (NCT02723552). Enrolment occurred between 30/06/2016-26/10/2018. Amongst the 203 randomized young adults (n = 102 in the intervention group; n = 101 in the control group), 178 (88%; n = 76 intervention group, n = 84 control group) completed 16-week follow-up and 160 (79%; n = 68 intervention group, n = 69 control group) completed 52-weeks follow-up. There were no group differences in awake systolic (0·0 mmHg [95%CI, -2·9 to 2·8]; P = 0·98) or awake diastolic ambulatory blood pressure (0·6 mmHg [95%CI, -1·4. to 2·6]; P = 0·58). Aerobic training increased peak oxygen uptake (2·8 ml/kg/min [95%CI, 1·6 to 4·0]) and peak wattage (14·2watts [95%CI, 7·6 to 20·9]) at 16-weeks. There were no intervention effects at 52-weeks follow-up. These results do not support the exclusive use of moderate to high intensity aerobic exercise training for blood pressure control in young adults. Wellcome Trust, British Heart Foundation, National Institute for Health Research, Oxford Biomedical Research Centre.